Systematic Review of the Surgical Treatment of Extremity Lymphedema - Carl, Hannah M.; Walia, Gurjot; Bello, Ricardo; Clarke-Pearson, Emily; Hassanein, Aladdin H.; Cho, Brian; Pedreira, Rachel; Sacks, Justin M. (Journal of Reconstructive Microsurgery, 2017)
Background Although conservative management of lymphedema remains the first-line approach, surgery is effective in select patients. The purpose of this study was to review the literature and develop a treatment algorithm based on the highest quality lymphedema research.Methods A systematic literature review was performed to examine the surgical treatments for lymphedema. Studies were categorized into five groups describing excision, liposuction, lymphovenous anastomosis (LVA), vascularized lymph node transfer (VLNT), and combined/multiple approaches. Studies were scored for methodological quality using the methodological index for nonrandomized studies (MINORS) scoring system.Results A total of 69 articles met inclusion criteria and were assigned MINORS scores with a maximum score of 16 or 24 for noncomparative or comparative studies, respectively. The average MINORS scores using noncomparative criteria were 12.1 for excision, 13.2 for liposuction, 12.6 for LVA, 13.1 for VLNT, and 13.5 for combined/multiple approaches. Loss to follow-up was the most common cause of low scores. Thirty-nine studies scoring > 12/16 or > 19/24 were considered high quality. In studies measuring excess volume reduction, the mean reduction was 96.6% (95% confidence interval [CI]: 86.2–107%) for liposuction, 33.1% (95% CI: 14.4–51.9%) for LVA, and 26.4% (95% CI: − 7.98 to 60.8%) for VLNT. Included excision articles did not report excess volume reduction.Conclusion Although the overall quality of lymphedema literature is fair, the MINORS scoring system is an effective method to isolate high-quality studies. These studies were used to develop an evidence-based algorithm to guide clinical practice. Further studies with a particular focus on patient follow-up will improve the validity of lymphedema surgery research.
Keywords: lymphedema; lymphovenous anastomosis; vascularized lymph node transfer